The making of the Second English Coronation Ordo. (26th April 2019) - Pratt, David
Abstract: This article reassesses the Second English Coronation Ordo in the light of its relationship to Carolingian sources. The dependence of the Ordo on a distinctive West Frankish source, here termed the Leiden Ordo, has many implications, since the Leiden Ordo seems likely to have been composed for the anointing of Charles the Straightforward by Fulk of Rheims in January 893. This finding provides a probable context for the importing of West Frankish ordines in King Alfred's dealings with Rheims. It also strengthens the case for placing the Second Ordo in the mid- or late 890s, rather than early in Athelstan's reign. Anointing practices were directly implicated in the 'crisis of authority' affecting the Carolingian world in the late ninth century. The new understanding of the Second Ordo adds a further dimension to King Alfred's efforts to promote the 'kingdom of the Anglo-Saxons', and has wider implications for the development of royal ordines in western Europe.